Education based on the theory of planned behavior to improve medication regimen adherence, hope and marital quality in patients with substance use disorder - Kamyab, Amirhossein; Bijani, Mostafa; Jormand, Hanieh; Harsini, Pooyan Afzali; Jeihooni, Ali Khani (BMC public health, 2024)
Background Regarding the psychosocial aspect of treating those with substance use, it is crucial for them to exhibit a capacity for personal transformation, fully utilize their remaining capabilities, and eradicate societal discrimination. We aimed to assess the efficacy of educational instruction grounded in the theory of planned behavior (TPB) in enhancing adherence to medication regimens, fostering hope, and improving marital quality among people with substance use disorders. Methods This study was conducted at the Rapid Addiction Closure Center in Fasa city, Iran, involving a sample of 140 patients undergoing addiction treatment with methadone and buprenorphine in 2021–2022. Subjects were randomly allocated to intervention and control groups. The intervention group participated in 15 weekly educational sessions, each lasting 50 to 55 min, covering topics such as quitting strategies, social support, problem solving, communication skills, and coping mechanisms. Data were collected using demographic questionnaires, TPB construct questionnaires, Miller’s Hope Survey, and the Revised Dyadic Adjustment Scale. Results The study included 140 individuals receiving treatment for addiction. No differences were seen among the two groups in education, occupation, marital status, and living conditions before the intervention. However, six months later, the intervention group showed improvements in attitude, subjective norms, perceived behavioral control, behavioral intention, medication regimen adherence, hope, and marital quality compared to controls. Conclusion The results indicate that family-based educational interventions grounded in TPB are effective in improving medication regimen adherence, hope, and marital quality among patients with substance use disorders. Significant increases in attitude, subjective norms, perceived behavioral control, and behavioral intention positively impacted medication regimen adherence in these patients.